Impact of tango on Parkinson’s disease - a narrative review - Muzyk, Magdalena; Duda, Weronika; Mrowczyk, Patrycja; Nowoświat, Patrycja; Bado, Michał; Goncerz, Michał; Bilecki, Krzysztof; Bednarczyk, Paulina; Pilawska, Sandra Agnieszka; Maślankiewicz, Maria; et al. (Quality in Sport, 2024)
Introduction: Parkinson’s disease (PD) is a fast-growing neurodegenerative condition caused by the deficiency of dopamine (Bloem et al., 2021). Main symptoms include tremor, bradykinesia, muscular rigidity and postural instability (Ye et al., 2023). Although PD treatment primarily involves pharmacotherapy, physical activity-based treatments such as tango dance can improve the quality of life of patients. Aim of the study: This narrative review aims to assess the impact of the therapeutic benefits of tango dance therapy for people with PD. Materials and methods: A comprehensive literature search was conducted in the PubMed database up to 2024. The review included randomised controlled trials, case reports, and pilot studies focused on the impact of tango on PD. Results: Several studies have evaluated the impact of tango on patients with PD. Some of them found that tango improves dynamic balance and walking, reduces the risk of falling, improves body awareness, stability, and emotional well-being among patients with PD. Conclusions: The impact of tango on PD is not yet conclusively documented, and further research is needed.